2008
DOI: 10.1590/s0006-87052008000300028
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade sensorial do café de lavouras em conversão para o sistema de produção orgânico

Abstract: Com o objetivo de se verificar a qualidade sensorial do café de lavouras em conversão para o sistema de produção orgânico, foi instalado este experimento, no município de Lavras (MG). O experimento foi instalado em 2004, em uma lavoura de café Catuaí Amarelo IAC 86, espaçamento de 4,0 x 0,6 m, com seis anos de idade, anteriormente cultivada no sistema convencional. Nos tratamentos orgânicos, empregou-se o delineamento látice balanceado 4 x 4, com cinco repetições em esquema fatorial 3 x 2 x 2, mais quatro trat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
1
0
2
Order By: Relevance
“…Similar results were obtained by Malta et al (2008), who verified the superiority of coffee beverages with the use of bovine manure alone or associated with coffee husks and green manure in coffee plantations in the second year of conversion in relation to conventional management, particularly in terms of sweetness, body and after taste.…”
Section: Resultssupporting
confidence: 84%
“…Similar results were obtained by Malta et al (2008), who verified the superiority of coffee beverages with the use of bovine manure alone or associated with coffee husks and green manure in coffee plantations in the second year of conversion in relation to conventional management, particularly in terms of sweetness, body and after taste.…”
Section: Resultssupporting
confidence: 84%
“…O sistema de produção adotado também pode interferir na qualidade do café. De acordo com Malta (2008), no segundo ano de conversão de lavouras convencionais para orgânicas foi observado efeitos significativos de práticas de adubação orgânica (com esterco bovino isolado ou associado com casca de café) e adubação verde sobre as qualidades sensoriais do café arábica. Batista (2007) afirma que é necessário conhecer os pontos críticos da colheita e póscolheita para conseguir minimizar a infestação de fungos nos grãos de café, que depreciam a qualidade da bebida por meio de fermentações indesejáveis ou são produtores de micotoxinas, notadamente a ocratoxina A. O autor ainda afirma, baseado em seus resultados, que os pontos críticos a serem combatidos são: a secagem em terreiros de terra, a colheita por meio de varrição e a secagem de café mistura (grãos cereja maduros, verdes e boia).…”
Section: Boas Práticas Agrícolas E Interferência Na Classificação Da ...unclassified
“…Furthermore, the drier climate in the months of August and September 2009 caused premature maturation of the beans (harvest in March and April 2010), further compromising the grain formation process, evidenced by the low yield achieved in 2010. In the literature, there are contradictory reports of the effect of organic fertilization on the productivity of coffee trees, e.g., Malta et al (2007) observed increase from 33 to 40.8 bg ha -1 with pigeon pea, as well as observed by Araujo et al (2014) with the jack bean. Theodoro, Mendes and Guimarães (2009) verified that coffee productivity was not influenced by applying this legume.…”
Section: Resultsmentioning
confidence: 93%